An investigation into the Effect of Alpha Ointment (Fundermol) on Perineal Pain relief Following Episiotomy in Nulliparous Women - Zahra Abedian; Mozhdeh Navinezhad; Javad Asili; Habibollah Esmaeili (Mashhad University of Medical Sciences, 2018)
Background & aim: Pain is the most common complaint of mothers after episiotomy. Various medications are used for the alleviation of this pain. The aim of this study was to evaluate the effect of alpha ointment on the relief of pain caused by episiotomy. Methods: This double-blind clinical trial was conducted on 70 primiparous women in Ommolbanin Hospital in Mashhad, Iran. The participants were divided into two groups of control and intervention. The intervention group received one fingertip unit of Alpha ointment following washing the wound with normal saline and drying, 48 hour after delivery, once a day, until the tenth day. The control group received a placebo in the same manner. Pain intensity was evaluated using the shortened from of McGill Pain Questionnaire on the first, fifth, and tenth days post-delivery. Data analysis was carried out in SPSS (version 16) using the Mann-Whitney U test, t-test, Chi-square test, and Fisher's exact test. Results: There was no statistically significant difference between the two groups in terms of the mean pain score on the first, fifth, and tenth days of the study (P=0.73, P=0.098, and P=0.464, respectively). Conclusion: As the finding of the present study showed, Alpha ointment had no effect on the perineal pain after episiotomy.